The Alternative Model Settlement of Credit Problems in Banking Agencies - Lukmanul Hakim (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
Currently, the bank had a very important and very strategic role in various fields, as mandated by Law No. 7 on 1992 as amended and added into Law No. 10 on 1998 concerning banking where the bank has the main function of collecting and channeling the funds back to the community. Currently, the community cannot be separated from the banking world because it is no longer a public secret that banking services are very helpful towards the economic activities, especially entrepreneurs who want to expand their business. The research method used to answer the problems in this research is to use the normative legal research approach which is also called theoretical legal research or dogmatic legal research because it does not study the implementation of legal imperative. Data processing is done by several stages, namely data selection, data classification, and data systematics. Furthermore, the data is processed and analyzed qualitatively. The results of research and discussion show that legal certainty made by the government as an effort to protect the banks and debtors while the efforts that can be taken in settlement of troubled banks can be made by reconditioning, restructuring, and rescheduling. Besides the existence of 3R as one of the problems solving loan models, there are also models of problem-solving loans such as selling collateral underhand or takeover. Keywords: Model Alternative Settlement, Credit, Problematic, Banking.